Pilot Testing and Preliminary Psychometric Validation of Situational Judgment Test of Resistance to Sunk Cost - Rahmat Hidayat; Muhammad Dwirifqi Kharisma Putra (Faculty of Psychology, Universitas Gadjah Mada, 2022)
The sunk-cost fallacy is an anomaly in decision-making that has been proven in various experimental studies. However, individual differences in the tendency to fall into sunk-cost fallacy have not been sufficiently reported. This preliminary study contains a psychometric evaluation report of the Resistance to Sunk Costs (RtSC) measurement instrument, a component of the Adult Decision Making Competence instrument (A-DMC; De Bruin, Parker, & Fischhoff, 2007) which is modified into Indonesian socio-cultural and economic contexts. The RtSC instrument uses a situational judgment test model, therefore it is adequate to measure the psychological construct of sunk-cost fallacy. The data analysis techniques used in this study were Item Factor Analysis (IFA) and graded response models. Respondents in this study were 217 students in Indonesia. The analysis results show that the 1-factor model of resistance to sunk costs fits the data. At the item level, based on the IFA, it was found that two out of ten items were found to be misfits. The results of the GRM analysis on the remaining eight items indicate that the items fit the GRM. However, the distinguishing power and reliability were found to be low. It can be concluded that this preliminary study provides a variety of important information as suggestions for improvement for our modified scale. Several theoretical and methodological implications are discussed.